Low-viscosity, high-strength and high-toughness environment-friendly grouting material and preparation method thereof
Through the design of two-component grouting materials, the SiO2 three-dimensional network structure and polyurethane hard section are generated by using sodium silicate aqueous solution and modified polymethylene polyphenyl polyisocyanate components, which solves the problem that existing grouting materials cannot achieve high strength and low viscosity at the same time, and achieves environmentally friendly grouting materials with low viscosity, high strength and high toughness, which are suitable for reinforcement and repair of a variety of engineering diseases.
Patent Information
- Application Number
- CN202411866758.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-11
AI Technical Summary
Existing grouting materials cannot achieve high strength and low viscosity at the same time, resulting in difficulty in penetration in fine gaps or soil.
A two-component grouting material is used, in which component A is an aqueous solution of sodium silicate and component B is a modified polymethylene polyphenyl polyisocyanate. The SiO2 three-dimensional network structure is formed by reacting NCO groups with water, combining with the hard section of the polyurethane compound, improving the strength and toughness of the material, and modifying the isocyanate component through hydrophilic polyether polyols to improve the compatibility of the AB component.
It realizes environmentally friendly grouting materials with low viscosity, high strength and high toughness, which can not foam in water environment. It is suitable for non-destructive reinforcement and repair of roadbeds, dams, tunnels and other diseases, and has excellent heat-resistant aging performance.
Smart Images

Figure CN119798596A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grouting materials, and in particular to a low-viscosity, high-strength, high-toughness, environmentally friendly grouting material and a preparation method thereof. Background Art
[0002] Grouting reinforcement technology is to use high-pressure devices to quickly inject grouting materials (such as cement slurry, chemical grouting materials, etc.) into the diseased project. Traditional chemical grouting materials often use cement slurry or water glass cement mixed grouting materials and other materials for grouting reinforcement. This type of grouting material has the characteristics of low cost and convenient and fast construction, but it also has the disadvantages of high brittleness, long gel time, long curing time, high viscosity and difficulty in penetrating into tiny gaps or even soil.
[0003] The prior art, such as the organic-inorganic hybrid grouting material for foaming water plugging recorded in patent number CN114380970B, has a high foaming expansion ratio, low density and good waterproof performance; because it is a foaming material, there are holes inside the material, so the strength of the material is not high; and the new chemical grouting material often uses polyurethane chemical grouting material, which has the characteristics of high strength of reinforcement material, good toughness, adjustable viscosity, adjustable gel time and curing time, and high bonding strength, but its cost is high and the physical properties of low-viscosity materials are lost. The preparation method of an organic-inorganic hybrid modified polyurethane chemical grouting material with patent number CN103012712A uses inorganic silicate modified polyurethane. Although it has high mechanical strength, the component viscosity ranges from 200-1500mpa·s, and there are few reports of silicate modified polyurethane materials with lower viscosity. Summary of the invention
[0004] The purpose of the invention is to provide a low-viscosity, high-strength, high-toughness, environmentally friendly grouting material and a preparation method thereof, which solves the problem that the grouting material in the prior art cannot achieve high strength and low viscosity at the same time.
[0005] The present invention is implemented as follows: a low-viscosity, high-strength, high-toughness, environmentally friendly grouting material comprises component A and component B, wherein component A comprises the following raw materials in parts by weight:
[0006] 90-100 parts of sodium silicate aqueous solution
[0007] Chain extender crosslinker 0-15 parts
[0008] First diluent 0-9 parts
[0009] Composite catalyst 0.85-2 parts
[0010] Component B includes the following raw materials in parts by weight:
[0011] 55-80 parts of polymethylene polyphenyl polyisocyanate
[0012] Polyether polyol 0-10 parts
[0013] Plasticizer 18-26 parts
[0014] The second diluent is 5-15 parts.
[0015] In the present invention, the isocyanate component contains NCO groups, which react with water to generate amino compounds and CO2. The generated CO2 reacts with sodium silicate to generate a three-dimensional network structure of SiO2 to form strength.
[0016] NCO-R-NCO+2H2O→H2N-R-NH2+2CO2
[0017] The amino compound further reacts with the isocyanate to form a substituted urea, which is the hard segment of the polyurethane compound and has a favorable effect on the strength and toughness of the polyurethane polymer.
[0018] NCO-R-NCO+H2N-R-NH2→NCO-R-NH-CO-NH-R-NH2
[0019] The reaction of isocyanate (NCO group) with linear difunctional polyether polyol can improve the toughness of the material, and the reaction with small molecule polyol (glycerol) can increase the crosslinking density of the material. Under the action of catalyst, the reaction generates carbamate, which is the hard segment of polyurethane compound and has a favorable effect on the strength and toughness of polyurethane polymer.
[0020]
[0021]
[0022] The grouting material A component of the present invention is an aqueous solution component, and the B component is an oily isocyanate component. The direct mixing effect of the two components is poor, so the B component needs to be modified. The key point of the modification of the isocyanate component is to increase the hydrophilicity, which can improve the compatibility of the AB components. Common measures to increase the hydrophilicity of the isocyanate component include using hydrophilic polyether prepolymerization, adding surfactants, adding solubilizers, etc.
[0023] Surfactants are added to hydrophilically modify isocyanates. The general practice is to add cationic or anionic hydrophilic modifiers. Cationic hydrophilic modifiers include quaternary ammonium salts, pyridinium salts, imidazolium salts, etc. The large-scale use of cationic hydrophilic modifiers will accelerate the reaction rate of the -NCO group in the system with water, resulting in faster production of more CO2, and then foaming and expansion problems, affecting the strength of the consolidated body; anionic modifiers often use carboxylates and sulfonates to hydrophilically modify isocyanates. This method will also lead to problems such as short service life and poor stability of the combined material to a certain extent.
[0024] Adding a solubilizer to perform hydrophilic modification of isocyanate has a certain effect. Although more solubilizers can further reduce the viscosity of the components, adding too much solubilizer is not a reactive component and will remain in the solid body after the mixing reaction of the AB components, which has a greater impact on the strength of the solid body.
[0025] Using hydrophilic polyether for prepolymerization can not only obtain a prepolymer with good hydrophilicity, but also the urethane hard segment generated by the reaction is beneficial to improving the strength of the solid body. The hydroxyl group on the hydrophilic polyether molecular chain will react with the -NCO group in the isocyanate component, so that the prepolymer molecular chain contains alkoxy groups, and the alkoxy groups can form hydrogen bonds with water, so the hydrophilicity of the modified isocyanate prepolymer can be improved. Most polyether polyols are prepared by different initiators, propylene oxide (PO) or PO and ethylene oxide (EO) blocks and end-capping agents, and the hydrophilicity of the polyether polyol prepared by PO is not as good as the polyether polyol of PO / EO ring-opening block copolymerization because of the branched methyl group after PO is opened. Therefore, the present invention adopts the polyether polyol of PO / EO ring-opening block copolymerization. As the hydrophilic segment of the prepolymer molecule becomes longer, the more alkoxy groups the prepolymer contains, the better the hydrophilicity, but the isocyanate component is easier to disperse in water, and the viscosity also increases, which is a disadvantageous factor for the present invention, so it is necessary to control the content of the hydrophilic segment of the prepolymer molecule. The 3Y-208 used in the present invention is a difunctional polyether diol containing 20% EO segment (hydrophilic segment), which is used for prepolymerization to prepare the isocyanate component, increase the hydrophilicity of the isocyanate component, thereby improving the compatibility of the AB two components, and at the same time ensure that the grouting material will not disperse in water.
[0026] A further technical solution of the present invention is that the composite catalyst includes DMP-30 and at least one of DMAEE and WNT05A.
[0027] In the present invention, the polymethylene polyphenyl polyisocyanate is actually a mixture of polymethylene polyphenyl polyisocyanates with different functionalities, wherein the monomer MDI usually accounts for 50%-55% of the total amount of the mixture, and the rest are oligomeric isocyanates with functionalities of 3-6.
[0028] The monomer MDI can self-polymerize to form a trimer under the action of heating (the reaction of NCO group with water and the gel reaction are both exothermic reactions) and the catalyst DMP-30.
[0029]
[0030] The 3-6 functional oligomeric isocyanates in polymethylene polyphenyl polyisocyanates can also self-polymerize to form trimers under heating (the reaction of NCO groups with water and the gel reaction are both exothermic reactions) and the action of catalyst DMP-30.
[0031]
[0032] The trimer is an isocyanate with a stable carbon-nitrogen six-membered ring structure. It contains multiple -NCO groups and is a high-functionality isocyanate. The high-functionality isocyanate can react with polyols under the action of a catalyst to generate a compound containing a carbamate and a carbon-nitrogen six-membered ring stable structure. The compound can continue the chain growth reaction to generate a polymer with high hardness and high cross-linking density. This polymer has excellent physical properties.
[0033]
[0034] The trimer has the properties of high thermal stability, high functionality, and low viscosity. ① Thermal stability: There is no active hydrogen in the six-membered ring structure of the trimer, and the ring structure is still stable above 200°C, especially the thermal decomposition temperature of the aromatic isocyanate ring structure can reach above 350°C. Based on this, the polymer material prepared by the present invention has excellent heat aging resistance. ② High functionality: The six-membered ring structure of the trimer contains multiple -NCO groups, which are highly active and highly polar. In addition to being introduced into the polymer by grafting reaction with active hydrogen compounds, it can also continue self-polymerization reaction to prepare polymers. ③ Low viscosity: Compared with the linear polymer generated by the reaction, the viscosity is lower, which is beneficial to increase the penetration range of the material.
[0035] The trimer can continue to self-polymerize under the action of a catalyst to generate a polymer:
[0036]
[0037] Polymers are hyperbranched polymers, which are similar to spherical structures. Compared with the chain structure of linear polymers, there are fewer molecular chains entangled, which means lower viscosity. Therefore, the viscosity of polymers is lower than that of traditional linear polyurethane polymers, and the penetration range is wider. At the same time, they have the same properties as trimers, such as high thermal stability, high functionality, and low viscosity. The polymer material has a high cross-linking density and good mechanical properties such as friction resistance and impact resistance.
[0038] Wherein, DMP-30 is the abbreviation of 2,4,6-tris(dimethylaminomethyl)phenol; DMAEE is the abbreviation of dimethylaminoethoxyethanol. WNT05A was purchased from Guangzhou Yourun Synthetic Materials Co., Ltd.
[0039] A further technical solution of the present invention is: the second diluent is propylene carbonate.
[0040] Compared with other diluents, the AB components will wrap around the diluent after the mixed reaction and curing, resulting in reduced material density and reduced physical properties. Propylene carbonate will hydrolyze into CO2 and propylene glycol after the AB components are mixed. The hydrolysis product can be used as a curing reactant to increase the density of the material after curing.
[0041] CO2 has a large solubility in propylene carbonate. In addition to being a diluent, propylene carbonate can also be used as an adsorbent for CO2. CO2 dissolved in propylene carbonate can continue to react with sodium silicate, reducing the adverse effects caused by the bubbling of CO2 gas. At the same time, propylene carbonate has a certain solubility in water. In an alkaline environment (sodium silicate solution is alkaline), it can undergo hydrolysis to produce CO2 and propylene glycol. The produced CO2 can further react with sodium silicate. Propylene glycol can react with isocyanate in the presence of a catalyst to produce carbamate. Carbamate is the hard segment of the polyurethane compound, which has a favorable effect on the strength and toughness of the polyurethane polymer.
[0042]
[0043] A further technical solution of the present invention is that the sodium silicate aqueous solution has a Baume degree of 40-50 and a modulus of 2.0-3.0.
[0044] The main component of sodium silicate aqueous solution is sodium silicate, and its chemical formula is Na2O·nSiO2. The modulus of sodium silicate is: n=SiO2 / Na2O (molar ratio). The modulus shows the composition of sodium silicate and is an important parameter of sodium silicate, which is generally between 1.5 and 3.5. The Baume degree of sodium silicate solution is positively correlated with its concentration. The larger the Baume degree, the higher the concentration and the greater the viscosity. The larger the modulus of sodium silicate, the lower its solubility in water and the higher its viscosity.
[0045] The reaction equation for sodium silicate solution absorbing CO2 is as follows:
[0046] Na2SiO3+CO2+H2O→Na2CO3+H2SiO3↓
[0047] The silicic acid generated by the reaction is unstable and can easily further associate into polysilicic acid:
[0048] H2SiO3+H2O→mSiO2·nH2O
[0049] Polysilicic acid will further condense into a three-dimensional network structure of SiO2 (inorganic silicate network structure):
[0050]
[0051] The inorganic silicate network structure has a high crosslinking density, which has an important influence on the strength of the material. The more the content per unit volume, the greater the material strength. The modulus in the sodium silicate solution has a greater influence on this reaction. The larger the modulus, the higher the SiO2 content. At the same time, the shorter the gel time of polysilicate formation, which has a positive effect on early strength and high strength.
[0052] A further technical solution of the present invention is that the chain extending cross-linking agent is a small molecule polyol.
[0053] The small molecule polyol is glycerol.
[0054] A further technical solution of the present invention is: the first diluent is pure water and / or a dispersant.
[0055] A further technical solution of the present invention is: the polymethylene polyphenyl polyisocyanate is PM-200.
[0056] A further technical solution of the present invention is: the polyether polyol model is at least one of polyether 3Y-208, 3Y-28-00, and 3Y-28-82.
[0057] A further technical solution of the present invention is that the plasticizer is dibutyl phthalate (DBP) and / or chlorinated paraffin.
[0058] The present invention also provides a method for preparing a low-viscosity, high-strength, high-toughness, environmentally friendly grouting material, the preparation method comprising the following steps:
[0059] Step 1, in 90-100 parts of sodium silicate aqueous solution, add 0-15 parts of chain extender crosslinking agent, 0-9 parts of first diluent, and 0.85-2 parts of composite catalyst in sequence under stirring, disperse evenly to obtain component A, and seal and store for standby use;
[0060] Step 2: Add 0-10 parts of polyether polyol, 18-26 parts of plasticizer and 5-15 parts of second diluent to 55-80 parts of polymethylene polyphenyl polyisocyanate under stirring, stir and disperse evenly at 60°C-80°C to obtain component B, and seal and store for later use.
[0061] Step 3: Mix the above-prepared component A and component B to obtain a low-viscosity, high-strength, high-toughness, environmentally friendly grouting material.
[0062] The beneficial effects of the present invention are as follows: the present invention is a two-component grouting material, comprising an organic phase and an inorganic phase. It is an organic-inorganic combination of low viscosity, high strength and high toughness, and an environmentally friendly grouting material. As a grouting material, the viscosity of the slurry has an important influence on the groutability and penetration range. The material of the present invention can have low viscosity, high strength and high toughness while maintaining relatively high physical properties, and will not foam when exposed to water. It can be used for trenchless and non-destructive reinforcement and repair of defects in roadbeds, dams, tunnels, and other water environments.
[0063] In the present invention, the isocyanate component contains NCO groups, and the NCO groups react with water to generate amino compounds and CO2, and the generated CO2 reacts with sodium silicate to generate a three-dimensional network structure of SiO2 to form strength. The amino compound further reacts with the isocyanate to generate substituted urea, which is the hard segment of the polyurethane compound and has a favorable effect on the strength and toughness of the polyurethane polymer. The isocyanate (NCO group) reacts with a linear difunctional polyether polyol to improve the toughness of the material, and reacts with a small molecule polyol (glycerol) to improve the crosslinking density of the material. Under the action of a catalyst, the reaction generates carbamate, which is the hard segment of the polyurethane compound and has a favorable effect on the strength and toughness of the polyurethane polymer.
[0064] The grouting material component A of the present invention is an aqueous solution component, and the component B is an oily isocyanate component. The direct mixing effect of the two components is poor, so the component B needs to be modified. Therefore, the present invention adopts a polyether polyol of PO / EO ring-opening block copolymerization. As the hydrophilic segment of the prepolymer molecule becomes longer, the more alkoxy groups the prepolymer contains, the better the hydrophilicity, but the isocyanate component is easier to disperse in water, and the viscosity also increases, which is a disadvantageous factor for the present invention, so it is necessary to control the content of the hydrophilic segment of the prepolymer molecule. The 3Y-208 used in the present invention is a difunctional polyether diol containing 20% EO segment (hydrophilic segment), which is used for prepolymerization to prepare the isocyanate component, increase the hydrophilicity of the isocyanate component, thereby improving the compatibility of the two components AB, and at the same time ensure that the grouting material will not disperse in water.
[0065] In the present invention, the polymethylene polyphenyl polyisocyanate is actually a mixture of polymethylene polyphenyl polyisocyanates with different functionalities, wherein the monomer MDI usually accounts for 50%-55% of the total amount of the mixture, and the rest are oligomeric isocyanates with functionalities of 3-6. The monomer MDI can self-polymerize to form a trimer under the action of heating (the reaction of the NCO group with water and the gel reaction are both exothermic reactions) and the catalyst DMP-30. The oligomeric isocyanates with functionalities of 3-6 in the polymethylene polyphenyl polyisocyanate can also self-polymerize to form a trimer under the action of heating (the reaction of the NCO group with water and the gel reaction are both exothermic reactions) and the catalyst DMP-30. The trimer is an isocyanate with a stable carbon-nitrogen six-membered ring structure, containing multiple -NCO groups, and is a high-functionality isocyanate. The high-functionality isocyanate can react with polyols under the action of a catalyst to generate a compound containing carbamate and a carbon-nitrogen six-membered ring stable structure. The compound can continue to undergo a chain growth reaction to generate a polymer with high hardness and high crosslinking density. This polymer has excellent physical properties. The trimer has the properties of high thermal stability, high functionality, and low viscosity. ① Thermal stability: There is no active hydrogen in the trimer six-membered ring structure, and the ring structure is still stable at temperatures above 200°C, especially the thermal decomposition temperature of the aromatic isocyanate ring structure can reach above 350°C. Based on this, the polymer material prepared by the present invention has excellent heat aging resistance. ② High functionality: The trimer six-membered ring structure contains 3 -NCO groups, which is highly active and polar. In addition to being introduced into the polymer by grafting reaction with active hydrogen compounds, it can also continue to self-polymerize to prepare polymers. ③ Low viscosity: Compared with linear polymers generated by the reaction, the viscosity is lower, which is beneficial to increase the penetration range of the material.
[0066] The trimer can continue to self-polymerize under the action of a catalyst to generate a polymer. The polymer is a hyperbranched polymer. The hyperbranched polymer is similar to a spherical structure. Compared with the chain structure of a linear polymer, the intermolecular chains are less entangled, which means the viscosity is lower. Therefore, the viscosity of the polymer is lower than that of a traditional linear polyurethane polymer and the penetration range is wider. At the same time, it has the same properties as the trimer, such as high thermal stability, high functionality, and low viscosity. The polymer material has a high cross-linking density and good mechanical properties such as friction resistance and impact resistance.
[0067] In the present invention, propylene carbonate will be hydrolyzed into CO2 and propylene glycol after the AB components are mixed, and the hydrolysis product can be used as a curing reactant to increase the density of the cured material. CO2 has a large solubility in propylene carbonate. In addition to being a diluent, propylene carbonate can be used as an adsorbent for CO2. CO2 dissolved in propylene carbonate can continue to react with sodium silicate, reducing the adverse effects caused by the bubbling of CO2 gas precipitation; at the same time, propylene carbonate has a certain solubility in water. In an alkaline environment (sodium silicate solution is alkaline), a hydrolysis reaction can occur to generate CO2 and propylene glycol. The generated CO2 can further react with sodium silicate. Propylene glycol can react with isocyanate under the action of a catalyst to generate carbamate. Carbamate is a hard segment of a polyurethane compound, which has a favorable effect on the strength and toughness of polyurethane polymers. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 The present invention provides a process flow chart of a method for preparing a low-viscosity, high-strength, high-toughness, environmentally friendly grouting material. DETAILED DESCRIPTION
[0069] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0070] A low-viscosity, high-strength, high-toughness, environmentally friendly grouting material, comprising component A and component B, characterized in that component A comprises the following raw materials in parts by weight:
[0071] 90-100 parts of sodium silicate aqueous solution
[0072] Chain extender crosslinker 0-15 parts
[0073] First diluent 0-9 parts
[0074] Composite catalyst 0.85-2 parts
[0075] Component B includes the following raw materials in parts by weight:
[0076] 55-80 parts of polymethylene polyphenyl polyisocyanate
[0077] Polyether polyol 0-10 parts
[0078] Plasticizer 18-26 parts
[0079] The second diluent is 5-15 parts.
[0080] The composite catalyst includes at least one of DMP-30 (2,4,6-tris(dimethylaminomethyl)phenol), DMAEE (dimethylaminoethoxyethanol) and WNT05A.
[0081] The second diluent is propylene carbonate.
[0082] The sodium silicate aqueous solution has a Baume degree of 40-50 and a modulus of 2.0-3.0.
[0083] The chain extending cross-linking agent is a small molecule polyol.
[0084] The first diluent is pure water and / or a dispersant.
[0085] The polymethylene polyphenyl polyisocyanate is PM-200.
[0086] The polyether polyol model is at least one of polyether 3Y-208, 3Y-28-00, and 3Y-28-82.
[0087] The plasticizer is dibutyl phthalate (DBP) and / or chlorinated paraffin.
[0088] In the following examples, the chain extending cross-linking agent is glycerol.
[0089] The polymethylene polyphenyl polyisocyanate in component B is PM-200, which is purchased from Wanhua Energy Saving Technology Group Co., Ltd.
[0090] As another embodiment, the polyether polyol may have a hydroxyl value in the range of 10-100 and a functionality of about 2.
[0091] The sodium silicate aqueous solution in component A is one of Baume 50A, modulus 2.7, Baume 45A, modulus 2.7, Baume 45A, modulus 2.3, and Baume 45A, modulus 2.0, and is purchased from Foshan Zhongfa Water Glass Factory.
[0092] The viscosity of the grouting material slurry has an important influence on the pourability and penetration range, and the cross-linking density of the solidified body after curing is also crucial to the strength and toughness of the material. To ensure a certain strength, it is very important to select the modulus and Baume degree of the sodium silicate solution. The organic phase (polyurethane network structure and trimer or polymer network structure) formed by the curing of the two components and the inorganic phase (inorganic silicate network structure) are interpenetrated to form a three-dimensional interpenetrating network structure, and the obtained solidified body has higher strength and better toughness. The specific embodiments are as follows
[0093] Embodiment 1-5:
[0094] Example 1-5 A low-viscosity, high-strength, high-toughness, environmentally friendly grouting material includes raw materials as shown in Table 1; the grouting material is prepared by the following method according to the raw materials recorded in Examples 1-5:
[0095] Step 1: Add 90-100 parts of sodium silicate aqueous solution into a dispersion tank, add 0-15 parts of glycerol, 0-9 parts of purified water, and 0.85-2 parts of composite catalyst in order while stirring, stir for 30 minutes to disperse evenly to obtain component A, and seal and store for later use;
[0096] Step 2: Add 55-80 parts of polymethylene polyphenyl polyisocyanate into a dispersion tank, add 0-10 parts of polyether polyol, 18-26 parts of plasticizer, and 5-15 parts of the second diluent in order while stirring, stir at a constant temperature of 60°C for 30 minutes to disperse evenly to obtain component B, and seal and store for later use.
[0097] Step 3: Fully mix the above-prepared component A and component B to obtain low-viscosity, high-strength, high-toughness, and environmentally friendly grouting materials corresponding to Examples 1-5, respectively.
[0098] The compressive strength and failure deformation performance tests were performed on the grouting materials obtained in Examples 1-5. The results are shown in Table 1.
[0099] Table 1 Mass fraction of each raw material and material performance test results of Examples 1-5
[0100]
[0101] Glycerol is called propylene glycol. One molecule of glycerol can provide three crosslinking points during the crosslinking process with isocyanate, which can make the polyurethane produce a network structure and further increase the hard segment content of the polyurethane, but it can also easily make the test block brittle, resulting in poor toughness. Compared with Example 2 and Example 3, Example 1 shows that the content of glycerol crosslinking agent is gradually increased, while the compressive strength is gradually reduced, the destructive resistance is also reduced, and the toughness is poor. It can be seen that when the concentration of sodium silicate is large, the R value is low, and increasing the crosslinking agent content is not beneficial to the strength.
[0102] Compared with Example 4, Example 1 increases the content of PM-200, improves the R value, and improves the compressive strength to 48.3 MPa and the failure deformation to 33.9%, indicating that increasing the R value is helpful to improve the compressive strength.
[0103] Compared with Example 5, Example 4 adds polyether glycol, the failure deformation is increased to 35.1%, and the compressive strength is maintained at 49.6 MPa.
[0104] Embodiment 6-11:
[0105] Example 6-11 A low-viscosity, high-strength, high-toughness, environmentally friendly grouting material includes raw materials as shown in Table 2; the grouting material is prepared by the following method according to the raw materials recorded in Example 6-11:
[0106] Step 1: Add 90-100 parts of sodium silicate aqueous solution into a dispersion tank, add 0-15 parts of glycerol, 0-9 parts of purified water, and 0.85-2 parts of composite catalyst in order while stirring, stir for 30 minutes to disperse evenly to obtain component A, and seal and store for later use;
[0107] Step 2: Add 55-80 parts of polymethylene polyphenyl polyisocyanate into a dispersion tank, add 0-10 parts of polyether polyol, 18-26 parts of plasticizer, and 5-15 parts of the second diluent in order while stirring, stir at a constant temperature of 60°C for 30 minutes to disperse evenly to obtain component B, and seal and store for later use.
[0108] Step 3: Fully mix the above-prepared component A and component B to obtain low-viscosity, high-strength, high-toughness, and environmentally friendly grouting materials corresponding to Examples 6-11, respectively.
[0109] The grouting materials obtained in Examples 6-11 were tested for compressive strength and destructive deformation performance. The product of Comparative Example 1 was purchased from Wanhua Energy Saving Technology Group Co., Ltd. The results are shown in Table 2.
[0110] Table 2: Mass fraction of each raw material and material performance test results of Examples 6-11
[0111]
[0112] The sodium silicate concentration was reduced from the original 50A to 45A, which can further reduce the viscosity of material A, reduce the content of catalyst WNT05A, increase the gel time, and thus help to increase the penetration range. Compared with Example 7, when other contents are the same, the sample obtained by using catalyst WNT05A is stronger and more ductile than that by using catalyst DMAEE.
[0113] Compared with Example 8, Example 6 adds a cross-linking agent, adds a trimerization catalyst DMP-30, increases the content of PM-200 to improve the R value, and improves the strength to 49.4 MPa. At the same time, the diluent propylene carbonate is used to reduce the viscosity of material B to 95 MPa·s while maintaining a high strength.
[0114] In Example 8, compared with Example 9 and Example 10, the use of a sodium silicate solution with a lower viscosity can further reduce the viscosity of material A, but the compressive strength is reduced too much and the material becomes more brittle.
[0115] In Example 8 compared with Example 11, the content of trimerization catalyst DMP-30 is increased, the viscosity of material A is reduced to 53 MPa·s, and the viscosity of material B is reduced to 53 MPa·s. At the same time, the loss of compressive strength is small, still greater than 40 MPa, reaching 43.5 MPa, and the destructive deformation reaches 39.72%. Compared with Comparative Example 1, the viscosity is similar, the strength is greater, and the toughness is higher.
[0116] The cured samples of the grouting material obtained by the above preparation method using the raw materials described in Example 11 were subjected to aging experiments in three environments: room temperature, 80°C constant temperature hot water, and 80°C constant temperature. The aging results are shown in Table 3:
[0117] Table 3 Experimental results of the grouting material solidification samples prepared from the raw materials in Example 11
[0118]
[0119] The above data indicate that the low-viscosity, high-strength, high-toughness, environmentally friendly grouting material prepared in the present invention has good heat aging resistance, the curing reaction is more complete during the heat aging process, and the strength is further increased, wherein the toughness is reduced after constant temperature aging at 80°C.
[0120] Embodiment 12:
[0121] A method for preparing a low-viscosity, early-strength, high-strength, high-toughness, environmentally friendly grouting material, specifically comprising the following steps:
[0122] (1) Add 90 parts of 27-45A sodium silicate aqueous solution to a dispersion tank, add 10 parts of glycerol, 0.8 parts of catalyst WNT05A, and 0.5 parts of trimerization catalyst DMP-30 in sequence while stirring, stir for 30 minutes to disperse evenly to obtain component A, and seal and store for later use.
[0123] (2) Add 71.25 parts of PM-200 to a dispersion tank, add 3.75 parts of polyether polyol 3Y-208, 20 parts of plasticizer DBP, and 5 parts of diluent propylene carbonate while stirring, and stir at a constant temperature of 60°C for 30 minutes to disperse evenly to obtain component B, which is sealed and stored for later use.
[0124] (3) The component A and the component B prepared above are fully mixed in a mass ratio of 1:1 to obtain a low-viscosity, early-strength, high-strength, high-toughness, and environmentally friendly grouting material.
[0125] The viscosity of the above-mentioned component A is 112 MPa·s, the viscosity of the component B is 95 MPa·s, and the solidified body obtained after the two components AB are mixed and cured in a 1:1 mass ratio has a 1-hour strength of 30.5 MPa, a 3-day strength of 52 MPa, and a destructive deformation of 38.6%. It can be used as an early strength and toughening rapid repair and reinforcement material.
[0126] In summary, the material in the present invention has the following advantages:
[0127] 1. Low viscosity. The viscosity of the AB component of the existing silicate-modified polyurethane grouting materials on the market is usually 200-300mpa·s. The viscosity of the AB component of the present invention can be as low as 53mpa·s, while still maintaining a relatively high strength.
[0128] 2. Early strength and high strength. Under low viscosity conditions, the compressive strength can reach up to 49.4MPa. The strength of the solidified body after AB mixing and curing is 30.5MPa in 1 hour, 52MPa in 3 days, and the destructive deformation is 38.6%. It can be used as an early strength and toughening rapid repair and reinforcement material.
[0129] 3. High toughness, low viscosity and high strength, the maximum compression deformation rate reaches 40.28%.
[0130] 4. It solidifies without foaming in water environment and maintains high physical properties, with a compressive strength of 43.5MPa and a maximum compression deformation rate of 39.72%.
[0131] 5. Excellent heat aging resistance without loss of strength.
[0132] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A low-viscosity, high-strength, high-toughness, environmentally friendly grouting material, comprising component A and component B, characterized in that: Component A includes the following raw materials in parts by weight: 90-100 parts of sodium silicate aqueous solution Chain extender crosslinker 0-15 parts First diluent 0-9 parts Composite catalyst 0.85-2 parts Component B includes the following raw materials in parts by weight: 55-80 parts of polymethylene polyphenyl polyisocyanate Polyether polyol 0-10 parts Plasticizer 18-26 parts The second diluent is 5-15 parts.
2. A low-viscosity, high-strength, high-toughness, environmentally friendly grouting material according to claim 1, characterized in that: The composite catalyst includes DMP-30 and at least one of DMAEE and WNT05A.
3. The low-viscosity, high-strength, high-toughness, environmentally friendly grouting material according to claim 1, characterized in that: The second diluent is propylene carbonate.
4. The low-viscosity, high-strength, high-toughness, environmentally friendly grouting material according to claim 1, characterized in that: The sodium silicate aqueous solution has a Baume degree of 40-50 and a modulus of 2.0-3.
0.
5. The low-viscosity, high-strength, high-toughness, environmentally friendly grouting material according to claim 1, characterized in that: The chain extending cross-linking agent is a small molecule polyol.
6. The low-viscosity, high-strength, high-toughness, environmentally friendly grouting material according to claim 1, characterized in that: The first diluent is pure water and / or a dispersant.
7. The low-viscosity, high-strength, high-toughness, environmentally friendly grouting material according to claim 1, characterized in that: The polymethylene polyphenyl polyisocyanate is PM-200.
8. The low-viscosity, high-strength, high-toughness, environmentally friendly grouting material according to claim 1, characterized in that: The polyether polyol model is at least one of polyether 3Y-208, 3Y-28-00, and 3Y-28-82.
9. The low-viscosity, high-strength, high-toughness, environmentally friendly grouting material according to claim 1, characterized in that: The plasticizer is dibutyl phthalate and / or chlorinated paraffin.
10. A method for preparing a low-viscosity, high-strength, high-toughness, environmentally friendly grouting material, characterized in that: The preparation method comprises the following steps: Step 1, in 90-100 parts of sodium silicate aqueous solution, add 0-15 parts of chain extender crosslinking agent, 0-9 parts of first diluent, and 0.85-2 parts of composite catalyst in sequence under stirring, disperse evenly to obtain component A, and seal and store for standby use; Step 2: Add 0-10 parts of polyether polyol, 18-26 parts of plasticizer and 5-15 parts of second diluent to 55-80 parts of polymethylene polyphenyl polyisocyanate under stirring, stir and disperse evenly at 60°C-80°C to obtain component B, and seal and store for later use. Step 3: Mix the above-prepared component A and component B to obtain a low-viscosity, high-strength, high-toughness, environmentally friendly grouting material.
Citation Information
Patent Citations
Method for preparing organic and inorganic hybridization modified polyurethane chemical grouting material
CN103012712A
An organic-inorganic hybrid grouting material for foamed water plugging and its preparation process
CN114380970B